Obstructive Sleep Apnea in People and Dogs and an Equine Perspective - Ahern , Tom (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Sleep deprivation had been well documented in human, canine and equine species. However the medical causes and consequences of this affliction appeared to be more thoroughly investigated in human and canine species. In these a link between obstructive sleep apnea with its associated sleep deprivation, and gastrointestinal and thermoregulatory health had been established along with a bidirectional association between gastrointestinal reflux disease and obstructive sleep apnea. Surgeries to reduce the incidence of obstructive sleep apnea had also been developed. However this condition was yet to be formally recognised in horses and therefore the potential benefit of surgical approaches had not been explored.In all three species the deleterious affects of sleep deprivation on emotional or psychological health had been established.